PLA-b-PEG/magnetite hyperthermic agent prepared by Ugi four component condensation - L. P. Icart; E. R. F. dos Santos; E. D. Pereira; S. R. Ferreira; V. Saez; J. A. Ramon; M. Nele; J. C. S. Pinto; R. D. Toledo; D. Z. Silva; F. G. Souza Jr (eXPRESS Polymer Letters, 2016)
Ugi four component condensation (UFCC), is an important tool for the synthesis of different types of bioconjugate species. In this study, a PLA-PEG/magnetite magnetic composite was prepared by a synthetic-route approach based on UFCC. In particular, poly(lactic acid) (PLA) was synthesized by autocatalytic polycondensation. Also, poly(ethyleneglycol) bis-amine (bis-amine PEG) was synthesized by two different methods: via carbonyldiimidazol (CDI)/ethylenediamine (ED) (75% yield) and via chlorate monochlorated acetyl (CCA)/ED (95% yield). All products were characterized by gel permeation chromatography (GPC), hydrogen-1 nuclear magnetic resonance (NMR 1H), Fourier transform infrared (FTIR), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). In addition, magnetite was prepared and modified to generate aldehyde groups which are also necessary for UFCC. This product was characterized by DSC, TGA, X-ray diffraction (XRD) and magnetic force (MF) techniques. Also, the magnetic composite PLA-PEG/magnetite was synthesized by UFCC. The calculated yield was equal to 80%. Furthermore, magnetic microspheres were prepared by the procedure of emulsion solvent-evaporation and characterized by scanning electron microscopy (SEM) and magnetic induction hyperthermia (MIH). The main contribution of these results is to propose a new application for UFCC in the preparation of biomasked magnetic drug delivery systems able to improve the cancer treatment and even the welfare of the patients.